2019
DOI: 10.1002/adom.201900239
|View full text |Cite
|
Sign up to set email alerts
|

Thickness‐Dependent Refractive Index of 1L, 2L, and 3L MoS2, MoSe2, WS2, and WSe2

Abstract: Since the isolation of thin transition metal dichalcogenides (TMDCs) by mechanical exfoliation, Mo-and W-based dichalcogenides have attracted attention because of their thicknessdependent optical properties. [1] In particular, these materials display an indirect-to-direct bandgap transition when their thickness is reduced to a single layer, thereby significantly increasing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
107
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(116 citation statements)
references
References 28 publications
7
107
0
2
Order By: Relevance
“…Several previous reports have shed light on the complex refractive index (or the complex dielectric function, where one can be calculated from the other) of monolayer and few-layer MoS 2 . [13][14][15][16][17] Many of these reports have been indirect calculations of the n and k values, whereas some direct measurements are performed only for a small bandwidth of the spectrum. Li et al reported the complex dielectric function of exfoliated monolayer TMDC materials, including MoS 2 , from reflection spectra using Kramers-Kronig analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports have shed light on the complex refractive index (or the complex dielectric function, where one can be calculated from the other) of monolayer and few-layer MoS 2 . [13][14][15][16][17] Many of these reports have been indirect calculations of the n and k values, whereas some direct measurements are performed only for a small bandwidth of the spectrum. Li et al reported the complex dielectric function of exfoliated monolayer TMDC materials, including MoS 2 , from reflection spectra using Kramers-Kronig analysis.…”
Section: Introductionmentioning
confidence: 99%
“… 21 To this respect, extensive studies are reported on the layer‐dependent optical properties of graphene 20 , 22 and MoS . 23 , 24 The importance of optical contrast (O.C.) of CrCl increases due to the reported Raman insensitivity on few layers.…”
Section: Introductionmentioning
confidence: 99%
“…18,[27][28][29][30][31] The reflectance/transmittance contrast spectrum is introduced to measure the exciton energy without explicitly measuring the bandgap. 26,[32][33][34][35] Therefore, a robust measurement system is required to accurately measure the exciton energy and bandgap.…”
Section: Introductionmentioning
confidence: 99%